Safety of Patient-Controlled Analgesia After Surgery in Children And Adolescents: Concerns And Potential Solutions - Ocay, Don Daniel; Otis, Annik; Teles, Alisson R.; Ferland, Catherine E. (Frontiers in Pediatrics, 2018)
Patient-controlled analgesia (PCA) is common practice for acute postoperative pain management. Postoperative PCA use decreases pain intensity and improves patient satisfaction when compared to non-PCA routes of medication administration. Although PCA has several advantages regarding efficacy and safety, adverse events remain a concern. Programming errors and protocols, patient monitoring, and PCA by proxy or with continuous infusion are recurring silent dangers of PCA use in children and adolescents. Innovative considerations need to be emphasized for future improvement of PCA devices for elective surgical patients. With technology within the healthcare setting advancing at a fast pace, smart pump technology is something to look forward to.